Extension of gamma, beta and hypergeometric functions - Özergin, Emine; Özarslan, Mehmet Ali; Altın, Abdullah (Elsevier B.V, 2011)
The main object of this paper is to present generalizations of gamma, beta and hypergeometric functions. Some recurrence relations, transformation formulas, operation formulas and integral representations are obtained for these new generalizations.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication
Keywords: Beta function, Confluent hypergeometric function; Mellin transform, Gamma function, MATHEMATICS, APPLIED